Preparation of nanosized coacervates of positive and negative starch derivatives intended for pulmonary delivery of proteins. Issue 13 (16th March 2016) - Barthold, S.; Kletting, S.; Taffner, J.; de Souza Carvalho-Wodarz, C.; Lepeltier, E.; Loretz, B.; Lehr, C.-M.
Abstract : Use of charged starch-derivatives as nanoscaled protein carriers and their in vitro evaluation. Abstract : Proteins and peptides represent a large fraction of the compounds currently in drug development pipelines. Their application however often depends on the use of carrier systems. Nanoparticles (NPs) are widely used such carrier systems for protein delivery. The aim of this study was to design a new drug delivery system (DDS), prepared under mild conditions in aqueous solution without the requirement of a stabilizer. The biodegradability and biocompatibility of the designed system was explored with a view to specifically determine its potential to facilitate the pulmonary delivery of proteins. As a first step, anionic and cationic water soluble starch-derivatives were synthesized. These starch polymers allowed for NP formation via coacervation, as well as protein loading. Physicochemical characterization of the prepared NPs was then carried out: NPs were found to have a narrow size distribution with an average size ranging from 140 to 350 nm, and a ζ -potential ranging from −10 to −35 mV, depending on the formulation conditions. In a proof of concept study, starch NPs were found to be readily degraded by the human enzyme α-amylase, and showed good biocompatibility with A549 cells after 4 h. Upon nebulization, NPs were seen to be internalized by air–liquid interface cultivated A549 cells as well as 16HBE14o − cells. To evaluate the ability of starch NPs to load proteins of various characteristics, NPs were loaded with four model proteins/peptides possessing different molecular weights and isoelectric points – IgG1, RNAse A, insulin, and vancomycin. The greatest loading was achieved in the case of vancomycin with up to 23% drug loading and 43% encapsulation efficiency, indicating an optimal loading of proteins with an isoelectric point close to the pH of the NP suspension. In conclusion, starch NPs prepared by the developed mild and straightforward technique show potential as a safe platform for pulmonary delivery of proteins and peptides.